The role of a tantalum interlayer in enhancing the properties of Fe3O4 thin films - Ngo, Hai Dang; Truong, Vo Doan Thanh; Le, Van Qui; Pham, Hoai Phuong; Pham, Thi Kim Hang (Beilstein Journal of Nanotechnology, 2024)
High spin polarization and low resistivity of Fe3O4 at room temperature have been an appealing topic in spintronics with various promising applications. High-quality Fe3O4 thin films are a must to achieve the goals. In this report, Fe3O4 films on different substrates (SiO2/Si(100), MgO(100), and MgO/Ta/SiO2/Si(100)) were fabricated at room temperature with radio-frequency (RF) sputtering and annealed at 450 °C for 2 h. The morphological, structural, and magnetic properties of the deposited samples were characterized with atomic force microscopy, X-ray diffractometry, and vibrating sample magnetometry. The polycrystalline Fe3O4 film grown on MgO/Ta/SiO2/Si(100) presented very interesting morphology and structure characteristics. More importantly, changes in grain size and structure due to the effect of the MgO/Ta buffering layers have a strong impact on saturation magnetization and coercivity of Fe3O4 thin films compared to cases of no or just a single buffering layer.
Keywords: buffer layer; Fe3O4; magnetite; RF magnetron sputtering; spintronic